Scandal at penn state - Crandall, William, 1956- (SAGE knowledge. Cases., 2016)
This case looks at the events surrounding the scandal of child abuse that erupted around a football coach at Penn State University. It examines the university's response in managing the crisis and asks questions of a culture that allowed abuse to carry on unchecked for so long.